Surveying Climate-Relevant Behavior Measurements, Obstacles, and Implications - Hadler, Markus; Klösch, Beate; Schwarzinger, Stephan; Schweighart, Markus; Wardana, Rebecca; Bird, David Neil (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book discusses the contribution of sociology and survey research to climate research. The authors address the questions of which behaviors are of climate relevance, who is engaging in these behaviors, in which contexts do these behaviors occur, and which individual perceptions and values are related to them. Utilizing survey research, the book focuses on the measurement of climate-relevant behaviors with population surveys and develops an instrument that allows a valid estimate of an individual's GHG emissions with a few core items. While the development of these instruments was based on surveys and qualitative interviews conducted in Austria, the instruments were subsequently tested in a set of 31 European countries, revealing the international relevance of such research. The book also concludes with a brief consideration of the effects of the COVID-19 crisis on environmental attitudes, situating the project globally.